A physical reason for higher pH of tropical rainwater - MUKHERJEE, A. K.; NAND, KRISHNA (MAUSAM, 1981)
pH measurements of monsoon rainwater in India indicate that pH values are near about 7.0 which is the neutral value of pure distilled water. However, similar measurements in Europe and USA yield much lower values which are close to the theoretically computed value of 5.65 at 20 deg. c. The above theoretical value is based on the assumption that dissolved carbon dioxide in rainwater is in equilibrium with the atmospheric carbon dioxide. An attempt has been made in this paper to explain the higher pH of tropical rain in terms of the temperature dependence of solubility and dissolution rate of carbon dioxide in rainwater.